Why so curious? Quantifying mechanisms of information seeking. (October 2020) - van Lieshout, Lieke LF; de Lange, Floris P; Cools, Roshan
Highlights: Curiosity is multifaceted in nature. The neural mechanisms of curiosity overlap with those of reward motivation and learning. We are curious about information that might reduce uncertainty about the world around us and updates our current model of the world. We are curious about information that will make us feel good and we tend to avoid information that will make us feel bad. Abstract : Humans devote a substantial part of their time to seeking and consuming information. Often, this information is directly relevant. However, we also seek out information without obvious direct purpose. Curiosity about this type of information is called 'non-instrumental curiosity'. In this review we ask why we are so curious about information that serves no direct purpose and address the psychological and neural mechanisms by which such apparently purpose-less curiosity is elicited. Non-instrumental curiosity is argued to fulfill (at least) two goals: to progressively reduce uncertainty about the world around us, and to accrue information that makes us feel good. We conclude by highlighting the promise of future psychopharmacological and neurochemical imaging studies of curiosity for elucidating the basis of both state and trait-related variation in curiosity. This is pertinent given the key implication of neurotransmitters like noradrenaline and dopamine in uncertainty reduction, reward motivation and cognitive effort.